The influence of molasses addition on the kinetics of alcoholic fermentation of whey using Kluyveromyces marxianus yeast - Damir Stanzer; Slobodan Grba; Vesna Stehlik-Tomas; Jasna Mrvčić (Mljekarstvo)
Kinetics of alcoholic fermentation by yeast Kluyveromyces marxianusZIM 75 in various media based on whey and molasses were monitored. The fermentations were performed under static and semiaerobic conditions at 34°C. Deproteinized whey and molasses were mixed in various proportions to give final sugar mass concentrations of 5%, 10% and 15% in medium. The experiments conducted showed that medium with 10 % of sugar (sucrose:lactose=1:1) is optimal for alcoholic fermentations in static and semiaerobic conditions. The best ethanol yield after 24 hours of fermentation was 4.05 % (V/V) in static conditions and 4.9 % (V/V) in semiaerobic conditions. The biomass yield was 7.78 g d.m./L in semiaerobic conditions and 3.19 g d.m./L in static conditions.